Rotational cooling of polar molecules by Stark-Tuned cavity resonance - Ooi, Chong Heng Raymond (2003)
A general scheme for rotational cooling of diatomic heteronuclear molecules is proposed. It uses a superconducting microwave cavity to enhance the spontaneous decay via Purcell effect. Rotational cooling can be induced by sequentially tuning each rotational transition to cavity resonance, starting from the highest transition level to the lowest one using an electric field. Electrostatic multipoles can be used to provide large confinement volume with essentially homogeneous background electric field.